2015
DOI: 10.4314/gmj.v48i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subjective well-being among older Ghanaians

Abstract: Background: Later years of life are accompanied by many physical, emotional and environmental changes which may impact on the well-being of the individual. Many factors are known to influence the subjective well-being of older adults, but most, if not all of this information was the result of studies in the Western world. This study aimed at obtaining and documenting the predictors of subjective well-being (SWB) among older Ghanaians. Methods: Data for the study was obtained from the WHO SAGE study. The single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Currently, there are no other studies showing the predictors of subjective health, happiness, and life satisfaction among healthy adolescent populations in an African context. A cross-sectional study involving elderly people in Ghana reported that age, sex, educational level, income, and ethnic background were significantly associated with subjective well-being (Calys-Tagoe et al 2014). A similar study on the elderly population in Nigeria found that socioeconomic status was the biggest indicator of quality of life (Gureje et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, there are no other studies showing the predictors of subjective health, happiness, and life satisfaction among healthy adolescent populations in an African context. A cross-sectional study involving elderly people in Ghana reported that age, sex, educational level, income, and ethnic background were significantly associated with subjective well-being (Calys-Tagoe et al 2014). A similar study on the elderly population in Nigeria found that socioeconomic status was the biggest indicator of quality of life (Gureje et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown subjective health and quality of life outcomes among older population and people living with disease conditions (Bishwajit et al 2017;Klotz et al 2018;Matsuguma et al 2018;Calys-Tagoe et al 2014;Ryan et al 2007). Currently, there are no other studies showing the predictors of subjective health, happiness, and life satisfaction among healthy adolescent populations in an African context.…”
Section: Discussionmentioning
confidence: 99%
“…That said, despite the importance of SWB in old age, its analysis remains limited in low-middle income countries (LMICs) [47]. The few studies exploring SWB among elderly in SSA (i.e., South Africa, Nigeria, Ghana), reveal that seniors with low socioeconomic status, few social supports and/or identify as a woman, are more likely to report poor SWB compared to their economically advantaged, socially connected, male counterparts [48][49][50][51]. An important point from these investigations is that more work needs to tease out the role of particular determinants in the relationship between SWB and aging across a wider range of geographic contexts [50,51].…”
Section: Aging and Subjective Wellbeingmentioning
confidence: 99%
“…The few studies exploring SWB among elderly in SSA (i.e., South Africa, Nigeria, Ghana), reveal that seniors with low socioeconomic status, few social supports and/or identify as a woman, are more likely to report poor SWB compared to their economically advantaged, socially connected, male counterparts [48][49][50][51]. An important point from these investigations is that more work needs to tease out the role of particular determinants in the relationship between SWB and aging across a wider range of geographic contexts [50,51]. These statements are buttressed by recent academic and systematic reviews calling for more work to investigate the possible moderating factors and pathways that shape SWB in old age, particularly in under-resourced contexts where substantive gaps in knowledge exist [13,52].…”
Section: Aging and Subjective Wellbeingmentioning
confidence: 99%
“…Personal factors found to be associated with health in older adults are age [12,13], gender [12,13,14,15,16], race/ethnicity [12,13], education attainment [13,17,18,19]; and employment [12]. Research conducted in Europe, Asia, Africa, and Latin America with aging populations found several economic and social factors associated with broad health and independence outcomes, including: reduced retirement pensions [20]; community involvement and social support [21,22,23]; housing conditions [22,24,25]; income level [17,22,26,27,28]; forced retirement [29]; and feeling discriminated [24].…”
Section: Introductionmentioning
confidence: 99%